Total Solution For Smart Traffic and Toll Roads Management in Indonesia - Recky , Pattiasina Jefry (Devotion : Journal of Research and Community Service, 2021)
The Ministry of Public Works and Public Housing has the task of carrying out government affairs in the field of public works and public housing to assist the President in administering the state government. One of the mandated functions in carrying out this task is to formulate and implement policies in the field of road administration in accordance with the provisions of laws and regulations, including the regulation of toll roads in Indonesia in accordance with Government Regulation No. 15 of 2005 concerning Toll Roads. The toll road is one of the vital means needed to increase efficiency in public services, logistics and industry which leads to economic efficiency. According to data released by the World Bank in 2019, losses due to traffic jams in Indonesia amounted to USD 4 billion, equivalent to an estimated IDR 56 trillion, more than that due to queuing at toll gates there is potential for losses for all business entities. To overcome this problem, Indonesia is preparing to implement a non-stop (touchless) toll payment system on the Multi Lane Free Flow (MLFF) system using RFID-based ETC (Electronic Toll Collection) Total Solution technology and the transaction process is carried out through a special application that can be accessed from the Internet. Integrate all departments with an IoT (Internet of thing) system. This payment system can eliminate the GTO function of toll entry and exit gates. In addition, the MLFF system using RFID-based ETC will recognize and identify vehicles and users. In addition to the RFID-based ETC system to increase the productivity and effectiveness of traffic management on toll roads, maintenance of toll roads and bridges is also very vital, therefore detecting road surface damage directly using sensors, CCTV cameras and UAV unmanned aerial vehicles. (Unmanned Aerial Vehicle) which has the advantages of high.